A case of ventricular flutter and fibrillation in a calf suffering from diarrhea - Abdullah BAŞOĞLU; Kürşat TURGUT (Eurasian Journal of Veterinary Sciences)
Ventricular flutter and fibrilation was diagnosed by means of EGG in a calf suffering from diarrhea for three days. The calf 'was dehydrated, emaciated and in moribund status. Evaluation of blood sample revealed hyperkalemia (1<2.5 mEq/L) and hyperchloremia (159 mEq/L). Serum Na+ (.156 mEq/L) and Ca++ (10.34 mg/dl) levels were within normal range. She died at thirty minutes after arrival. At necropsy, there was no any organic disorder in the heart.